Application of an amplitude-integrated EEG monitor (cerebral function monitor) to neonates - Bruns, Nora; Müller, Hanna (JoVE. Video journal, 2017)
Here, we show how to apply amplitude-integrated electroencephalography to monitor cerebral function in neonates.
Enthält auch Textversion "Application of an amplitude-integrated EEG monitor (cerebral function monitor) to neonates" als pdf, 7 Seiten
Gesehen am 06.09.2018
Wissenschaftlicher Film. Deutschland. 2017
Keywords: Film